Compendium of school laws in the Philippines - Sarmiento, Ulpiano P. III (Ulpiano P. Sarmiento III, 2015)
"This book is the compendium of education of laws in the Philippines into 3 separate volumes to reflect the development that the Commission on Higher Education (CHED), the Department of Education (DepEd) and the Technical Education and Skills Development Authority (TESDA). Each volume contains the most recent and complete compilation of the laws, rules, regulations, and decisions affecting Philippine Education. Among others, the Enhanced Basic Education Law or the K to 12 Law, the Anti-Bullying Law, the Universal Kindergarten Law as well as the landmark decisions of the Supreme Court until December of 2014, are included."--Preface.